A Trip to the 2025 International Conference on the Anthropology of Salt - Drexler, Carl (Rzeszów University Press, 2025)
This article is an account of the travels of one participant in the 2025 International Conference on the Anthropology of Salt. Visits to the salt mine at Hallstatt, Austria, the conference in Rzeszow, and the salt mine heritage site at Wieliczka are discussed, with attention given to a comparison of the two mines and their presentation.